Effects of neural mobilization of sciatic nerve and its branches in plantar foot pressures and stabilometry - Martínez-Jiménez, Eva María; Losa-Iglesias, Marta Elena; Becerro-de-Bengoa-Vallejo, Ricardo; Rodríguez-Sanz, David; Calvo-Lobo, César; Jiménez-Fernández, Raquel; Corral-Liria, Inmaculada; Pérez-Boal, Eduardo; Navarro-Flores, Emmanuel (Scientific reports, 2024)
Benefits of neural mobilization (NM) have been described in musculoskeletal patients. The effects of NM on balance appear to be unclear in research, and no studies have tested the possible effects of NM on plantar pressures. Eighteen subjects were evaluated pre and post bilateral gliding of the sciatic nerve and its branches posterior tibial nerve, lateral dorsocutaneous, medial and intermediate dorsocutaneous nerves. Static variables of the plantar footprint and stabilometric variables were measured in a pre-post study. We found no differences in plantar pressure variables, Rearfoot maximum pressure ( p = 0.376), Rearfoot medium pressure ( p = 0.106), Rearfoot surface ( p = 0.896), Midfoot maximum pressure ( p = 0.975), Midfoot medium pressure ( p = 0.950), Midfoot surface ( p = 0.470) Forefoot maximum pressure ( p = 0.559), Forefoot medium pressure( p = 0.481), Forefoot surface ( p = 0.234), and stabilometric variables either, X-Displacement eyes-open ( p = 0.086), Y-Displacement eyes-open ( p = 0.544), Surface eyes-open ( p = 0.411), Medium speed latero-lateral displacement eyes-open ( p = 0.613), Medium speed anteroposterior displacement eyes-open ( p = 0.442), X Displacement eyes-closed ( p = 0.126), Y-Displacement eyes-closed ( p = 0.077), Surface eyes-closed ( p = 0.502), Medium speed latero-lateral displacement eyes-closed ( p = 0.956), Medium speed anteroposterior displacement eyes-closed ( p = 0.349). All variables don´t have significant differences however the measurements had a high reliability with at least an ICC of 0.769. NM doesn´t change plantar pressures or improve balance in healthy non-athletes subjects. NCT05190900.